Niche modelling to guide conservation actions in France for the endangered crayfish Austropotamobius pallipes in relation to the invasive Pacifastacus leniusculus - Préau, Clémentine (2020)
The white‐clawed crayfish (Austropotamobius pallipes) is globally endangered due to the impacts of habitat modification and fragmentation, water pollution, climate change, and invasive species, particularly the signal crayfish (Pacifastacus leniusculus). These pressures have caused the decline of A. pallipes populations in Europe, demonstrating the importance of predicting the species' potential distribution under current and future conditions. Focusing on the watercourses of mainland France, we aimed to identify suitable areas for A. pallipes to guide the conservation of current populations and future introduction actions or protection measures. 2. We applied ecological niche modelling to model the potential distribution of both A. pallipes and P. leniusculus and identified locations suitable for A. pallipes only. We also assessed the potential distribution of the species under two representative concentration pathway (RCP) scenarios: RCP 2.6 and RCP 8.5, respectively describing low‐warming and high‐warming conditions. 3. We found that A. pallipes and P. leniusculus exploit equivalent niches in France. Despite this, under current conditions, about 5% of the study area simultaneously records a high suitability for A. pallipes and a low suitability for P. leniusculus and is therefore of significant conservation interest. This percentage remains relatively stable under RCP 2.6 for 2050 and 2100, but decreases to 2% under RCP 8.5 for 2100. 4. Ecological niche modelling can supply crucial guidance for conservation actions aimed at protecting endangered species at a national scale by identifying sites most suitable for protection and sites where climate change and invasive species constitute a threat.